Impact of Social Media Activity on Consumer’s Brand Trust: A Meta-Analysis Study From a Communication Perspective - Hartati, Sri; Karim, Edwin; Rashid, Ibrahim (Business Review and Case Studies, 2025)
Background: Social media marketing is an important part of business operations in the modern era. Social media provides businesses with the ability to engage with broader and more diverse customers than the technology before it. Therefore, it is important to examine the impact of trust as an important part of the relationship between firms and customers. Purpose: This study aims to interpret and summarize the impact of social media marketing activity on brand trust through a meta-analysis of previous studies.. Design/methodology/approach: The researcher will employ meta-analysis to examine the impact of media marketing on customer trust. Meta-regression is employed to examine potential moderators that can influence the relationship. Findings/results: The meta-analysis result shows that there is a significant positive relationship between social media marketing activity and brand trust. Moderator analysis also shows that IT reliance in the industry may moderate this relationship, the specificity of IT utilization and its role in the business may cause this effect. Conclusion: The enhanced communication between brands and consumers that happens through social media can help brands develop a trusting relationship. Easier and more direct communication with customers allows brands to directly respond and address complaints or customer ideas more frequently. This feature of social media can help brands develop a more trustworthy image. Furthermore, the variety of utilization and importance of social media marketing’s role in building trust may vary depending on the business context. Originality/value: This research summarizes the result of previous research regarding trust in social media. Several moderating variables are examined to explain the phenomenon. Keywords: social media, digital marketing, marketing communication, brand trust, meta-analysis